Daisy. - Renald Taurusdi. (2010)
Daisy is a 3D short animated film that portray a quarrel between Old Lady and Bull over a daisy flower in a comical and humorous way. The animation intends to refresh the audiences by showing them how one little misunderstanding can be so mischievous. The team, consists of two young man who dream to inspire people, give their best to produce this short animation.